2014
DOI: 10.2139/ssrn.2394547
|View full text |Cite
|
Sign up to set email alerts
|

Special Economic Zones 20 Years Later

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
(9 reference statements)
0
8
0
2
Order By: Relevance
“…For decades, countries like China [52] dominated industrialization because of the availability of cheaper and skilled labor [26]. Experts give symmetrical preferences to the level of skill of labor that was considered critical [28,34,36,37]. The Chinese model of development using labor-intensive and low tech is suitable for countries like Pakistan because of its ability to accommodate local manufacturing without hefty trade deficit or unbearable debts that are undesirable consequences of heavy industrialization [83].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For decades, countries like China [52] dominated industrialization because of the availability of cheaper and skilled labor [26]. Experts give symmetrical preferences to the level of skill of labor that was considered critical [28,34,36,37]. The Chinese model of development using labor-intensive and low tech is suitable for countries like Pakistan because of its ability to accommodate local manufacturing without hefty trade deficit or unbearable debts that are undesirable consequences of heavy industrialization [83].…”
Section: Discussionmentioning
confidence: 99%
“…For the main factor labor (LO) the Symmetry 2020, 12, 242 9 of 23 authors selected three sub-criteria, i.e. wage rate (LO1) in the particular region [30,31], unemployment rate (LO2) of surrounding localities [24,28,59], and their level of skill (LO3) [28,34,36,37]. Market orientation (MA) determines the objectivity of the SEZ.…”
Section: Factor Identification and Enrichment By Delphi Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on location decisions finds that the quality of infrastructure and service and industry agglomeration are the main factor attracting foreign firms, while special economic zones have no effect (Cieślik, 2005). Jensen and Winiarczyk (2014), on the other hand, find a positive effect of special economic zones on business creation that comes mainly from FDI, while the effects on employment, investment and income generation are small or insignificant, suggesting that the policy has not been successful in creating a sustainable, positive dynamic, helping poorer regions to catch up. This finding is in contrast to Cizkowicz et al's (2015) work.…”
Section: Agglomerations With Strong Firm Network Training and Coachmentioning
confidence: 99%
“…Another study by Ambroziak (2015) suggests that there was no impact of the zones policy on the unemployment rate at the level of poviats. A study by Jensen and Winiarczyk (2014) using a simple difference-in-difference estimator showed that there was a small but positive effect of the zones policy on employment at the gmina (LAU2 -see footnote 1 further below) level. While the study by Cizkowicz et al is biased as a de facto policy evaluation in view to its emphasis on spillovers from only those zones that exhibit a positive development in terms of direct employment effects, the other available more traditional policy evaluation studies have in common that the policy variable lacks variability in the time dimension of its application.…”
Section: Previous Findings On Employment Effects Of Zones Type Policiesmentioning
confidence: 99%